Platinum-nickel alloy / carrier type catalyst as well as preparation method and application thereof
By preparing a platinum-nickel alloy catalyst on a TiO2 support, the existing precious metal catalysts have been solved, and the effect of efficient preparation of hydrocarbon-based biodiesel under mild conditions is achieved.
Patent Information
- Application Number
- CN202411333745.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2025-02-14
AI Technical Summary
The existing precious metal catalysts have problems such as poor catalytic activity, low selectivity of target alkanes and high temperature and high pressure in the oil and fat hydrogenation reaction.
The platinum-nickel alloy/support type catalyst was prepared by mixing TiO2 with soluble Pt salt and soluble Ni salt, and conducting hydrothermal reaction-induced alloy formation. The Pt and Ni loading amounts of the catalyst are 8% to 13% by weight, and the molar ratio is 1 to 3:1.
The catalyst operates under milder reaction conditions (100°C to 120°C, 0.2 to 0.4MPa), which significantly improves the catalytic activity, stability and selectivity of the target product, achieving a conversion rate of 100% and deoxygenation of more than 90% or more and nearly 80% of the C8-C17 target alkane selectivity.
Smart Images

Figure CN119425723A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalysts, and in particular to a platinum-nickel alloy / carrier type catalyst and a preparation method and application thereof. Background Art
[0002] Biojet fuel is usually made by hydroprocessing waste or non-edible oil into C8-C 16 Alkanes are produced (patents CN114196429A, CN112457878B, CN115138370B, etc.). In this process, a catalyst is usually required to participate in the reaction. However, the catalyst used in traditional thermal catalytic hydrogenation is mainly a metal-supported molecular sieve catalyst, for example, Ni / Al2O3, Ni / SAPO-11, Ni / SBA-15, Pt / SAPO-11. However, non-precious metal catalysts have some disadvantages, such as low catalytic activity, poor stability and selectivity. In order to solve the above problems, researchers have gradually turned their attention to precious metal catalysts.
[0003] At present, most precious metal catalysts are loaded with platinum, palladium, etc., so as to obtain precious metal / carrier type multifunctional catalysts. TiO2 plays a vital role in photocatalysts and has been widely used in the fields of environmental purification and energy conversion. It can be used as a catalyst carrier to provide a large specific surface area and a suitable pore structure to enhance the performance of the catalyst; in addition, TiO2 has excellent thermal stability and is suitable for catalytic reactions under high temperature conditions. Then studies have shown that the oil hydrogenation reaction is mainly carried out in the form of hydrodeoxygenation, hydrodecarboxylation, and hydrodecarbonylation, among which the hydrodeoxygenation reaction will produce water, which will lead to catalyst poisoning and deactivation. The catalyst with precious metal Pt as the active metal loaded on TiO2 is mainly carried out in the form of hydrodecarboxylation and hydrodecarbonylation during the oil hydrogenation reaction, which effectively avoids the formation of water. However, catalysts prepared by loading only single metal or bimetal on the carrier, such as Pt / TiO2, Ni / TiO2, Pt-Ni / TiO2 and other catalysts, have the disadvantages of poor catalytic activity, low selectivity of target alkanes, and the reaction usually requires high temperature and high pressure. Existing research mostly regulates metal sites by adding metal additives, or changes the type of carrier to change the number of acid sites. However, the addition of metal additives will cause particles to agglomerate, and some carriers are expensive and require high equipment, which is not conducive to industrial production. Summary of the invention
[0004] The purpose of the present invention is to provide a platinum-nickel alloy / carrier type catalyst and a preparation method and application thereof in view of the above-mentioned deficiencies in the prior art.
[0005] The invention discloses a method for preparing a platinum-nickel alloy / carrier-type catalyst. The method comprises the following steps: mixing TiO2, a soluble Pt salt and a soluble Ni salt, and then subjecting the mixture to a hydrothermal reaction to induce alloy formation to obtain an alloy solution; and filtering and drying the alloy solution and then calcining the alloy solution to obtain a platinum-nickel alloy / carrier-type catalyst.
[0006] Furthermore, the loading amount of Pt and Ni is 8wt% to 13wt%.
[0007] Furthermore, the molar ratio of Pt to Ni is 1 to 3:1.
[0008] Further, weigh Pt and Ni soluble salts and place them in a container; add TiO2 powder, organic solvent and reducing agent, mix them thoroughly and then carry out hydrothermal reaction; the hydrothermal reaction temperature is 160-180°C and the time is 5-8h.
[0009] Furthermore, the soluble Pt salt is at least one of chloroplatinic acid, tetraammineplatinum nitrate, and potassium chloroplatinite; the soluble Ni salt is at least one of nickel formate and nickel nitrate; the organic solvent is dimethylformamide and ethylene glycol; and the reducing agent is ascorbic acid.
[0010] Furthermore, the calcination temperature is 450-500° C. and the calcination time is 120-200 min.
[0011] Furthermore, the heating rate of calcination is 4-6°C / min.
[0012] A platinum-nickel alloy / carrier type catalyst prepared by the above preparation method.
[0013] An application of the platinum-nickel alloy / carrier catalyst as described above in the preparation of hydrocarbon-based biodiesel by oil hydrodeoxygenation.
[0014] Furthermore, the reaction temperature of the hydrodeoxygenation is 100° C. to 120° C., and the hydrogen pressure is 0.2 to 0.4 MPa; and the oils and fats include animal and plant oils and fats.
[0015] Compared with the prior art, the present invention has the following advantages:
[0016] 1. The catalyst prepared by the present invention exhibits unique advantages: the particle size of the alloy nanoparticles is controlled at 4-5nm, which is smaller than that of other catalysts and exhibits better performance. These alloy nanoparticles are not only evenly dispersed and precisely sized, but also exhibit significant high efficiency in terms of activity, stability and selectivity of target products.
[0017] 2. The present invention uses bimetallic catalysts to form alloys for loading. This design significantly improves the overall performance of the catalyst. Compared with single metal catalysts, alloy catalysts can achieve synergistic effects, enhance catalytic activity, and improve reaction efficiency. This alloy structure not only optimizes the electron distribution, but also increases the number of active sites, thereby showing stronger stability and anti-poisoning ability during the catalytic process.
[0018] 3. In the process of catalyzing oil and fat to prepare high-quality hydrocarbon-based biodiesel, the prepared catalyst can work under milder reaction conditions, such as lower temperature (100°C to 120°C) and pressure (0.2 to 0.4MPa), which not only reduces energy consumption, but also reduces equipment investment and operating costs.
[0019] 4. When the molar ratio of Pt to Ni is 3:1, the alloy nanoparticles have a unique octahedral cubic crystal phase, and have a conversion rate of nearly 100%, a deoxidation rate of more than 90%, and a C8-C 17 Target alkane selectivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 X-ray diffraction patterns (XRD) of the catalysts synthesized in Comparative Examples 1-3 and Example 4 of the present invention;
[0021] Figure 2 A high resolution transmission electron microscopy (HRTEM) image of the catalyst synthesized in Example 3 of the present invention;
[0022] Figure 3 High resolution transmission electron microscopy (HRTEM) images of the catalysts synthesized in Comparative Examples 1-3;
[0023] Figure 4 A high resolution transmission electron microscopy (HRTEM) image of the catalyst synthesized in Example 1;
[0024] Figure 5 This is a high-resolution transmission electron microscopy (HRTEM) image of the catalyst prepared with activated carbon as the carrier. DETAILED DESCRIPTION
[0025] The following are specific embodiments of the present invention and the accompanying drawings to further describe the technical solution of the present invention, but the present invention is not limited to these embodiments.
[0026] Comparative Example 1
[0027] Take 2g of TiO2 carrier and 20mg of Pt(NH3)4(NO3)2, place them in a polytetrafluoroethylene liner, and add 10-15ml of deionized water dropwise, stirring to mix evenly; then transfer to a stainless steel reactor and hydroheat in an oven at 180℃ for 5h; dry the hydroheated sample at 80℃ overnight, then heat it to 450℃ at a heating rate of 5℃ / min, keep the temperature constant for 150min, cool it naturally, and finally grind and seal the obtained sample to obtain a Pt / TiO2 catalyst with an active metal content of 5wt%, numbered B1.
[0028] Comparative Example 2
[0029] Take 2g of TiO2 carrier and 30mg of Ni(HCO2)2, place them in a polytetrafluoroethylene liner, and add 10-15ml of deionized water dropwise, stirring to mix evenly; then transfer to a stainless steel reactor and hydroheat in an oven at 180℃ for 5h; dry the hydroheated sample at 80℃ overnight, then heat it to 450℃ at a heating rate of 5℃ / min, keep the temperature constant for 150min, cool it naturally, and finally grind and seal the obtained sample to obtain a Ni / TiO2 catalyst with an active metal content of 5wt%, numbered B2.
[0030] Comparative Example 3
[0031] Take 2g of TiO2 carrier, 20mg of Pt(NH3)4(NO3)2, and 30mg of Ni(HCO2)2, place them in a polytetrafluoroethylene liner, and add 10-15ml of deionized water dropwise, stirring to mix evenly; then transfer them to a stainless steel reactor and hydroheat them in an oven at 180℃ for 5h; dry the hydroheated sample at 80℃ overnight, then heat it to 450℃ at a heating rate of 5℃ / min, keep the temperature constant for 150min, cool it naturally, and finally grind and seal the obtained sample to obtain a Pt-Ni / TiO2 catalyst with an active metal content of 10wt%, numbered B3.
[0032] Example 1
[0033] Take 50 mg of TiO2 carrier, 5 mg of Pt(NH3)4(NO3)2, 4.8 mg of Ni(HCO2)2, and 35.6 mg of ascorbic acid, place them in a polytetrafluoroethylene liner, and add 5 ml of dimethylformamide and 5 ml of ethylene glycol drop by drop, and stir to mix evenly; then transfer them to a stainless steel reactor and hydroheat them in an oven at 180°C for 5 hours; dry the hydroheated sample at 80°C overnight, then heat it to 450°C at a heating rate of 5°C / min, keep the temperature constant for 150 minutes, cool it naturally, and finally grind and seal the obtained sample to obtain a Pt3Ni / TiO2 alloy catalyst with an active metal content of 8wt%, numbered A1.
[0034] Example 2
[0035] Take 50 mg of TiO2 carrier, 8 mg of Pt(NH3)4(NO3)2, 4.8 mg of Ni(HCO2)2, and 35.6 mg of ascorbic acid, place them in a polytetrafluoroethylene liner, and add 5 ml of dimethylformamide and 5 ml of ethylene glycol drop by drop, and stir to mix evenly; then transfer them to a stainless steel reactor and hydroheat them in an oven at 180°C for 5 hours; dry the hydroheated sample at 80°C overnight, then heat it to 450°C at a heating rate of 5°C / min, keep the temperature constant for 150 minutes, cool it naturally, and finally grind and seal the obtained sample to obtain a Pt3Ni / TiO2 alloy catalyst with an active metal content of 11wt%, numbered A2.
[0036] Example 3
[0037] Take 50 mg of TiO2 carrier, 10 mg of Pt(NH3)4(NO3)2, 4.8 mg of Ni(HCO2)2, and 35.6 mg of ascorbic acid, place them in a polytetrafluoroethylene liner, and add 5 ml of dimethylformamide and 5 ml of ethylene glycol drop by drop, and stir to mix evenly; then transfer them to a stainless steel reactor and hydroheat them in an oven at 180°C for 5 hours; dry the hydroheated sample at 80°C overnight, then heat it to 450°C at a heating rate of 5°C / min, keep the temperature constant for 150 minutes, cool it naturally, and finally grind and seal the obtained sample to obtain a Pt3Ni / TiO2 alloy catalyst with an active metal content of 13wt%, numbered A3.
[0038] Example 4
[0039] Take 50 mg of TiO2 carrier, 10 mg of Pt(NH3)4(NO3)2, 4.8 mg of Ni(HCO2)2, and 35.6 mg of ascorbic acid, place them in a polytetrafluoroethylene liner, and add 5 ml of dimethylformamide and 5 ml of ethylene glycol drop by drop, and stir to mix evenly; then transfer them to a stainless steel reactor and hydroheat them in an oven at 200°C for 5 hours; dry the hydroheated sample at 80°C overnight, then heat it to 450°C at a heating rate of 5°C / min, keep the temperature constant for 150 minutes, cool it naturally, and finally grind and seal the obtained sample to obtain a Pt3Ni / TiO2 alloy catalyst with an active metal content of 13wt%, numbered A4.
[0040] Example 5
[0041] Take 50 mg of TiO2 carrier, 10 mg of H2PtCl6, 4.8 mg of Ni(HCO2)2, and 35.6 mg of ascorbic acid, place them in a polytetrafluoroethylene liner, and add 5 ml of dimethylformamide and 5 ml of ethylene glycol drop by drop, and stir to mix evenly; then transfer them to a stainless steel reactor and hydroheat them in an oven at 180°C for 5 hours; dry the hydroheated sample at 80°C overnight, then heat it to 450°C at a heating rate of 5°C / min, keep the temperature constant for 150 minutes, cool it naturally, and finally grind and seal the obtained sample to obtain a Pt3Ni / TiO2 alloy catalyst with an active metal content of 13wt%, numbered A5.
[0042] Example 6
[0043] Take 50 mg of TiO2 carrier, 10 mg of K2PtCl6, 4.8 mg of Ni(HCO2)2, and 35.6 mg of ascorbic acid, place them in a polytetrafluoroethylene liner, and add 5 ml of dimethylformamide and 5 ml of ethylene glycol drop by drop, and stir to mix evenly; then transfer them to a stainless steel reactor and hydroheat them in an oven at 180°C for 5 hours; dry the hydroheated sample at 80°C overnight, then heat it to 500°C at a heating rate of 5°C / min, keep the temperature constant for 150 minutes, cool it naturally, and finally grind and seal the obtained sample to obtain a Pt3Ni / TiO2 alloy catalyst with an active metal content of 11wt%, numbered A6.
[0044] Example 7
[0045] Take 50 mg of TiO2 carrier, 10 mg of H2PtCl6, 4.8 mg of Ni(NO3)2, and 35.6 mg of ascorbic acid, place them in a polytetrafluoroethylene liner, and add 5 ml of dimethylformamide and 5 ml of ethylene glycol drop by drop, and stir to mix evenly; then transfer them to a stainless steel reactor and hydroheat them in an oven at 180°C for 5 hours; dry the hydroheated sample at 80°C overnight, then heat it to 500°C at a heating rate of 5°C / min, keep the temperature constant for 150 minutes, cool it naturally, and finally grind and seal the obtained sample to obtain a Pt3Ni / TiO2 alloy catalyst with an active metal content of 13wt%, numbered A7.
[0046] Example 8
[0047] Take 50 mg of TiO2 carrier, 10 mg of K2PtCl6, 4.8 mg of Ni(NO3)2, and 35.6 mg of ascorbic acid, place them in a polytetrafluoroethylene liner, and add 5 ml of dimethylformamide and 5 ml of ethylene glycol drop by drop, and stir to mix evenly; then transfer them to a stainless steel reactor and hydroheat them in an oven at 180°C for 5 hours; dry the hydroheated sample at 80°C overnight, then heat it to 450°C at a heating rate of 5°C / min, keep the temperature constant for 150 minutes, cool it naturally, and finally grind and seal the obtained sample to obtain a Pt3Ni / TiO2 alloy catalyst with an active metal content of 11wt%, numbered A8.
[0048] Example 9
[0049] Take 50 mg of TiO2 carrier, 10 mg of Pt(NH3)4(NO3)2, 4.8 mg of Ni(HCO2)2, and 35.6 mg of ascorbic acid, place them in a polytetrafluoroethylene liner, and add 5 ml of dimethylformamide and 5 ml of ethylene glycol drop by drop, and stir to mix evenly; then transfer them to a stainless steel reactor and hydroheat them in an oven at 180°C for 6 hours; dry the hydroheated sample at 80°C overnight, then heat it to 450°C at a heating rate of 5°C / min, keep the temperature constant for 150 minutes, cool it naturally, and finally grind and seal the obtained sample to obtain a Pt3Ni / TiO2 alloy catalyst with an active metal content of 13wt%, numbered A9.
[0050] Example 10
[0051] Take 50 mg of TiO2 carrier, 10 mg of Pt(NH3)4(NO3)2, 4.8 mg of Ni(HCO2)2, and 35.6 mg of ascorbic acid, place them in a polytetrafluoroethylene liner, and add 5 ml of dimethylformamide and 5 ml of ethylene glycol drop by drop, and stir to mix evenly; then transfer them to a stainless steel reactor and hydroheat them in an oven at 180°C for 7 hours; dry the hydroheated sample at 80°C overnight, then heat it to 450°C at a heating rate of 5°C / min, keep the temperature constant for 150 minutes, cool it naturally, and finally grind and seal the obtained sample to obtain a Pt3Ni / TiO2 alloy catalyst with an active metal content of 13wt%, numbered A10.
[0052] like Figure 1-4 As shown, from the XRD and HRTEM images of the synthesized catalyst, it can be seen that the alloy nanoparticles prepared in the embodiment of the present invention have uniform particle distribution and a particle size of about 4-5 nm; the catalyst prepared in the comparative example does not form an alloy, and its nanoparticles are all irregular in shape.
[0053] The TiO2 carrier in Example 3 was replaced with an activated carbon carrier, and the other aspects were exactly the same as in Example 3. The HRTEM image of the catalyst prepared was as follows: Figure 5 As shown. (Since TiO2 has poor electrical conductivity and cannot present a clear morphological structure, the alloy was loaded on activated carbon for filming to facilitate the study of its structure).
[0054] like Figure 2 and Figure 5 As shown, when the ratio of Pt to Ni is 3:1, its structure has a unique octahedral cubic phase and the elements are evenly distributed.
[0055] Hydrogenation reaction evaluation results
[0056] Oleic acid was used as the reaction raw material, and the catalysts synthesized in Comparative Examples 1 to 10 were used to evaluate the hydrogenation catalytic reaction. The reaction conditions were: 120° C., hydrogen pressure 0.4 MPa, rotation speed 1000 r / min, reaction time 12 h, and raw material / catalyst ratio 5:1. The results are shown in Table 1.
[0057] Table 1. Evaluation results of hydrogenation reactions of different catalysts in Examples 1-10
[0058]
[0059]
[0060] Table 2. Evaluation results of hydrogenation reactions of different catalysts in Comparative Examples 1-3
[0061]
[0062] The present invention uses a hydrothermal method to form an alloy through reasonable regulation and load it on a TiO2 carrier to prepare a highly dispersed, small-particle multifunctional alloy catalyst for oil hydrogenation reaction to prepare biodiesel. The catalyst can achieve a 100% conversion rate, a deoxidation rate of more than 90% and nearly 80% C8-C 17 Alkane selectivity.
[0063] For matters not mentioned above, the prior art applies.
[0064] Although some specific embodiments of the present invention have been described in detail through examples, those skilled in the art should understand that the above examples are for illustration only and are not intended to limit the scope of the present invention. Those skilled in the art to which the present invention belongs may make various modifications or supplements to the specific embodiments described or replace them in a similar manner, but they will not deviate from the direction of the present invention or exceed the scope defined by the attached claims. Those skilled in the art should understand that any modifications, equivalent substitutions, improvements, etc. made to the above embodiments based on the technical essence of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a platinum-nickel alloy / carrier-type catalyst, characterized in that: TiO2 is mixed with a soluble Pt salt and a soluble Ni salt, and then a hydrothermal reaction is carried out to induce alloy formation to obtain an alloy solution; the alloy solution is filtered, dried, and then calcined to obtain a platinum-nickel alloy / carrier-type catalyst.
2. The preparation method according to claim 1, characterized in that: The loading amount of Pt and Ni is 8wt% to 13wt%.
3. The preparation method according to claim 1, characterized in that: The molar ratio of Pt to Ni is 1 to 3:
1.
4. The preparation method according to claim 1, characterized in that: Weigh Pt and Ni soluble salts and place them in a container; add TiO2 powder, organic solvent and reducing agent, mix thoroughly and then carry out hydrothermal reaction; the hydrothermal reaction temperature is 160-180°C and the reaction time is 5-8h.
5. The preparation method according to claim 3, characterized in that: The soluble Pt salt is at least one of chloroplatinic acid, tetraammineplatinum nitrate, and potassium chloroplatinite; the soluble Ni salt is at least one of nickel formate and nickel nitrate; the organic solvent is dimethylformamide and ethylene glycol; and the reducing agent is ascorbic acid.
6. The preparation method according to claim 3, characterized in that: The calcination temperature is 450-500°C and the time is 120-200 minutes.
7. The preparation method according to claim 3, characterized in that: The heating rate of calcination was 4-6°C / min.
8. A platinum-nickel alloy / carrier type catalyst prepared by the preparation method according to any one of claims 1 to 7.
9. Use of the platinum-nickel alloy / supported catalyst as claimed in claim 8 in the preparation of hydrocarbon-based biodiesel by hydrodeoxygenation of oils and fats.
10. The use according to claim 9, characterized in that: The reaction temperature of the hydrodeoxygenation is 100° C. to 120° C., and the hydrogen pressure is 0.2 to 0.4 MPa; the oils and fats include animal and plant oils and fats.
Citation Information
Patent Citations
A device and process for preparing second-generation biodiesel based on waste oil hydrodeoxygenation
CN112457878B
Catalyst for bio-oil hydrodeoxygenation and its preparation and application
CN115138370B
Cited By
Platinum-nickel alloy catalyst with high activity and high stability, preparation method and application of platinum-nickel alloy catalyst in water electrolysis hydrogen evolution reaction in acid medium
CN122169138A